Abortion laws reform may reduce maternal mortality: an ecological study in 162 countries - Su Mon Latt; Allison Milner; Anne Kavanagh (BMC, 2019)
Abstract Background Unsafe abortion is one of the commonest causes of maternal mortality. Abortion-related maternal deaths are higher in countries with the most restrictive abortion laws. We assess whether maternal mortality varies within and between countries over time according to the flexibility of abortion laws (the number of reasons a woman can have an abortion). Method We conducted an ecological study to assess the association between abortion laws and maternal mortality in 162 countries between 1985 and 2013. Aggregate-level data on abortion laws and maternal mortality were extracted from United Nations (UN), and World Health Organization's (WHO) database respectively. A flexibility score of abortion laws (Score 0-7) was calculated by summing the number of reasons for which abortion was legally allowed in each country. The outcome was maternal mortality ratio (MMR), which represented maternal deaths per 100,000 live births. MMR was modelled as a continuous variable and flexibility score as an ordinal ranked variable (categories 0-7 with 0 as the reference, and < 3 vs > = 3). We used fixed effects linear regression models to estimate the association between flexibility score and MMR, adjusting for gross domestic product per capita (GDP per capita), and time in five-year intervals. Results Compared to when a country's flexibility score was < 3, maternal deaths were reduced by 45 per 100,000 live births (95% CI: -64, − 26) when the flexibility score increased ≥3, after adjusting for the GDP per capita and five-year time intervals. With the exception of a flexibility score 6, MMR was lower when higher than zero. This may indicate the role of other country- specific effects. Conclusion This study provides evidence that abortion law reform in countries with restricted abortion laws may reduce maternal mortality.